Analysis Of Digital Marketing, Brand Image And Green Business On Business Sustainability In Retail MSMEs - ,, Hasanudin; ,, Nurhasan; Sucipto, Acip (Dinasti Publisher, 2025)
This research aims to find out whether digital marketing has an effect on business sustainability, to see the influence of brand image on business sustainability and to see the influence of green business on the sustainability of retail MSME businesses. The population in this research is retail MSME entrepreneurs in Cikeas Udik, Bogor Regency in 2024 after Covid-19. Samples were taken of 30 MSME entrepreneurs using the Slovin formula. The data collection technique was carried out by distributing questionnaires. The analysis techniques used in this research are partial test (t test), simultaneous significance test (F test), multiple linear regression and coefficient of determination. The research results state that digital marketing has a positive influence on business sustainability, brand image has a positive influence on business sustainability, while green business has a negative influence on business sustainability. This research looks at digital marketing through social media, increasing brand image which can create consumer loyalty, as well as increasing knowledge related to green marketing for the sustainability of retail MSME businesses based on environmental sustainability.